Induction of cardiac dysfunction in developing and adult zebrafish by chronic isoproterenol stimulation. (July 2017) - Kossack, Mandy; Hein, Selina; Juergensen, Lonny; Siragusa, Mauro; Benz, Alexander; Katus, Hugo A.; Most, Patrick; Hassel, David
Abstract: Zebrafish is a widely used model to evaluate genetic variants and modifiers that can cause heart muscle diseases. Surprisingly, the β-adrenergic receptor (β-AR) pathway in zebrafish is not well characterized, although abnormal β-AR signaling is a major contributor to human heart failure (HF). Chronic β-AR activation in the attempt to normalize heart function in the failing heart results in a reduction of the β-ARs expression and receptor desensitization, largely mediated through G-protein coupled receptor kinase 2 (GRK2) upregulation. This in turn leads to further deterioration of heart function and progression towards HF. This study seeks to systematically characterize the function of the β-AR signaling in developing and adult zebrafish to ultimately assess the ability to induce HF through chronic β-AR activation by isoproterenol (ISO) as established in the mouse model. Larval hearts first responded to ISO by 3 dpf, in concordance with robust expression of key components of the β-AR signaling pathway. Although ISO-induced β1-AR and β2-AR isoform upregulation persisted, chronic ISO stimulation for 5 d caused systolic cardiac dysfunction concurrently with maximal expression of G-protein-coupled receptor kinase-2 (GRK2). More consistent to mammalians, adult zebrafish developed significant heart failure in concert with β1-AR downregulation, and GRK2 and brain natriuretic peptide (BNP) upregulation in response to prolonged, 14 d ISO-stimulation. This was accompanied by significant cell death and inflammation without detectable fibrosis. Our study unveils important characteristics of larvae and adult zebrafish hearts pertaining to β-AR signaling. A lack of β-AR responsiveness and atypical β-AR/GRK2 ratios in larval zebrafish should be considered. Adult zebrafish resembled the mammalian situation on the functional and molecular level more closely, but also revealed differences to dysfunctional mammalian hearts, i.e. lack of fibrosis. Our study establishes the first ISO-inducible HF model in adult zebrafish and present critical characteristics of the zebrafish heart essential to be considered when utilizing the zebrafish as a human disease and future drug discovery model. Highlights: β-AR activation in zebrafish is comparable to mammals with limitations in larvae. Adult zebrafish remarkably resemble mammalian β-AR function. Chronic ISO induced myocardial damage seems irreversible in adult zebrafish. Adult ISO induced heart failure induces apoptosis and inflammation. ISO provoked heart failure lacks detectable hypertrophy and fibrosis.